Digital financial inclusion and its dual impact on economic and environmental outcomes in ASEAN countries - Farooq Ahmad Bajwa; Jingtao Fu; Ishtiaq Ahmad Bajwa; Manzar Rehman; Karim Abbas (Data Science in Finance and Economics)
We examined the influence of digital financial inclusion (DFI) on economic growth and environmental sustainability in ASEAN nations from 2005 to 2022. Employing advanced econometric techniques such as Pooled Ordinary Least Squares (POLS), Two-Stage Least Squares (2SLS), and Generalized Method of Moments (GMM), we uncovered compelling findings: DFI boosts the economy but at an environmental cost. This surprising outcome poses a significant challenge for policymakers striving to balance economic benefits with ecological health. Our study calls for strategic government action to reconcile these critical areas, ensuring sustainable regional development.